Enhanced carbon tolerance of Ir alloyed Ni-Based metal for methane partial oxidation - Ahn, K.; Lee, J.-H.; Kim, H.; Kim, J. (Cell Press, 2018)
Carbon plugging of active catalytic sites significantly degrades the performance of the hydrocarbon reformers. In this study, we show that small amount of Ir alloyed to Ni/CeO2 nanoparticle exhibit promising improvements to the carbon tolerance properties. XRD analysis indicates that the synthesized nanoparticles are comprised of independent NiO and CeO2 particulates and that the added Ir atoms tend to stay on the surface consistent with the theoretical calculation results of the proposed Ir-Ni alloy. The Ir rich samples show higher methane cracking rate and better carbon removal characteristics. Also, the CO selectivity result shows that adding Ir can prolong the lifetime of the Ni active sites despite a slight drop in the initial partial oxidization reforming rate. Our findings highlight the enhancement effects of Ir on the Ni-based metal carbon tolerance properties and bring us one step closer to finding a solution for the carbon plugging problem. ？ 2018 The Authors